Sustainable management system: Action research at Clos de Tres Cantos - Martínez-Valladares, María Fernanda; Serrato De La Cruz, María De Lourdes (LACCEI, 2025)
In this research a case study and action research approach are used to implement a sustainability management system in the Clos de Tres Cantos winery. Public and private documents were analyzed completed with interviews. During the planning stage, co-created with internal stakeholders took place to design and implement interventions. This is a qualitative study and during its development it was identified that the CEMEFI maturity model helps the establishment of an iterative sustainability management system. Additionally, the study highlights the relevance of organizational elements such as culture, interest, and commitment in advancing sustainability maturity. This is a unique case; therefore, its results cannot be considered generalizable, but they do provide in-depth documentation of the analyzed organization’s experience